CFD simulation of sucrose flow field in the stem of greenhouse tomato seedling - Ni, Jiheng; Dong, Jingtao; Ullah, Ikram; Mao, Hanping (International Journal of Agricultural and Biological Engineering, 2022)
Sucrose is the main constituent of assimilation transport from source to sink. In order to study the transport mechanism of sucrose, the sucrose at stem was taken as a research object and the sucrose flow field in tomato stem was analyzed using CFD ANSYS FLUENT simulation. The results showed that the sucrose pressure distribution was lower at bottom node and higher at middle node. The velocity of sucrose at different nodes was higher at the bottom node and lower at middle node and assimilation flow direction of the first, second, and third leaf from the bottom was towards the roots. The result of verification experiment showed that sucrose content measured at different nodes was higher at middle node than that of bottom node. Results of this study confirmed that ANASYS FLUENT can better simulate sucrose migration in greenhouse tomato stem. This study provides a new method for studying the partitioning mechanism of tomato assimilates in greenhouse. Keywords: greenhouse tomato, sucrose flow field, computational fluent dynamic, rule of distribution DOI: 10.25165/j.ijabe.20221501.6061 Citation: Ni J H, Dong J T, Ullah I, Mao H P. CFD simulation of sucrose flow field in the stem of greenhouse tomato seedling. Int J Agric & Biol Eng, 2022; 15(1): 111–115.